2017
DOI: 10.1016/j.jpsychires.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Do cognitive schema mediate the association between childhood trauma and being at ultra-high risk for psychosis?

Abstract: Exposure to childhood trauma has been associated with psychotic symptoms, being at ultra-high risk for psychosis (UHR), and psychotic disorders such as schizophrenia. Negative self-beliefs have been shown to partially mediate the relationship between childhood trauma and paranoia and have been shown to be characteristic of patients with psychosis. However, whether the association between childhood trauma and being at high risk of developing psychosis (e.g., UHR) and paranoia symptoms is mediated by altered cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 57 publications
2
45
1
1
Order By: Relevance
“…That is, the association between adverse neighborhood conditions and early expressions of psychosis is detectable at the level of the eye of the beholder. This is consistent with psychological theories and empirical studies of psychosis aetiology which emphasize the key role played by negative beliefs about the world and other people, hostile attributions of the intentions of others, and threat anticipation (An et al, 2010; Appiah-Kusi et al, 2017; Fowler et al, 2006; Freeman, 2016; Garety et al, 2007; Noone et al, 2015) in the development of psychotic experiences, such as paranoia; together with a broader literature suggesting that subjective perceptions of early-life adversity are associated with mental health problems over and above more objective reports of adversity exposure (Brown et al, 2005; Reuben et al, 2016; Widom & Morris, 1997; Widom et al, 1999). …”
Section: Discussionsupporting
confidence: 88%
“…That is, the association between adverse neighborhood conditions and early expressions of psychosis is detectable at the level of the eye of the beholder. This is consistent with psychological theories and empirical studies of psychosis aetiology which emphasize the key role played by negative beliefs about the world and other people, hostile attributions of the intentions of others, and threat anticipation (An et al, 2010; Appiah-Kusi et al, 2017; Fowler et al, 2006; Freeman, 2016; Garety et al, 2007; Noone et al, 2015) in the development of psychotic experiences, such as paranoia; together with a broader literature suggesting that subjective perceptions of early-life adversity are associated with mental health problems over and above more objective reports of adversity exposure (Brown et al, 2005; Reuben et al, 2016; Widom & Morris, 1997; Widom et al, 1999). …”
Section: Discussionsupporting
confidence: 88%
“…When serious forms of abuse take place, it is likely to convey the message that the child's core self is a disappointment because he or she has not lived up to expectations, or is simply not worthy of love and attention (Cecil et al, 2017). This notion aligns with research from cognitive models of psychosis used within clinical and nonclinical samples (Appiah-Kusi et al, 2017). Evidence suggests that childhood maltreatment may create an enduring cognitive vulnerability, characterized by negative schematic models of the self and the world that facilitates appraisal biases and low self-esteem, particularly if criticism stems directly from family members (Barrowclough et al, 2003;Garety, Bebbington, Fowler, Freeman, & Kuipers, 2007;Garety et al, 2001;Tiernan, Tracey, & Shannon, 2014).…”
Section: Discussionmentioning
confidence: 88%
“…As of yet, research has focused inter alia on dissociative factors (Kilcommons & Morrison, 2005), external locus of control (Bentall & Fernyhough, 2008), attachment styles Korver-Nieberg, Berry, Meijer, de Haan, & Ponizovsky, 2015), basic self-disturbances (Gawęda, Pionke, et al, 2018), anxiety (Freeman & Fowler, 2009), cognitive affect regulation strategies (Hardy et al, 2016) and cognitive biases (Gawęda, Pionke, et al, 2018;Kilcommons & Morrison, 2005) with special emphasis put to negative self-schemas, that are often observed in people suffering from psychosis. In their study, Appiah-Kusi et al (2017) found that negative self-schemas partially mediate the relationship of emotional neglect with UHR state of psychosis and paranoia. Similar results were obtained by Fisher, Appiah-Kusi, and Grant (2012), who demonstrated that recent anxiety and negative self-beliefs partially accounted for the association between emotional or physical abuse in childhood and paranoia.…”
mentioning
confidence: 93%